2017
DOI: 10.5603/kp.a2016.0097
|View full text |Cite
|
Sign up to set email alerts
|

Salivary B-type natriuretic peptide: a new method for heart failure diagnosis and follow-up

Abstract: A b s t r a c tBackground: Frequent hospital admissions and reduced quality of life are the main complications of heart failure (HF). Plasma B-type natriuretic peptide (BNP) levels have been considered as a cost-effective method of screening for left ventricular dysfunction. Studies regarding BNP-guided therapy revealed reduction in death or hospital stay for HF. Aim:As saliva has fewer limitations than blood in regard to sampling, the aim of the present study was to test if salivary BNP concentration might be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 24 publications
0
15
0
5
Order By: Relevance
“…The level of plasma BNP is a cost-effective method for evaluating the LV dysfunction. And some studies presented that BNP-guided therapies showed a decrease in death and hospital stay of CHF patients [34]. That means BNP is positively associated with all-cause mortality of CHF, and researchers also found that the standard of BNP was useful in estimating prognosis in stable CHF patients [35].…”
Section: Discussionmentioning
confidence: 99%
“…The level of plasma BNP is a cost-effective method for evaluating the LV dysfunction. And some studies presented that BNP-guided therapies showed a decrease in death and hospital stay of CHF patients [34]. That means BNP is positively associated with all-cause mortality of CHF, and researchers also found that the standard of BNP was useful in estimating prognosis in stable CHF patients [35].…”
Section: Discussionmentioning
confidence: 99%
“…So far, no studies evaluated the significance of salivary ANP in heart failure, but for NT-proBNP and BNP first studies were conducted. Those indicate that adult heart failure patients present higher levels than controls (53, 54). Saliva offers the advantages of being non-invasive, less demanding and easier to handle than blood.…”
Section: Anp In Pediatric Heart Failurementioning
confidence: 91%
“…The concentrations of other 3 antigens (cathelicidin, B‐natriuretic peptide (BNP), and cardiac troponin I (cTnI)) were maintained at 10 p m to study the effect of device performance and selectivity for IL‐6 and CRP in the presence of functionally, morphologically, and chemically different antigens under same concentration of targeted antigen. Cathelicidin, [ 64 ] BNP, [ 65 ] and cTnI [ 66 ] were reported to be present in human saliva and the concentrations of these antigens in human saliva is increased especially in the event of a cardiovascular disease. It is important to note that a significantly high resistance change was observed for the targeted antigen from the corresponding antibody‐immobilized device in the presence of antigen mixture.…”
Section: Figurementioning
confidence: 99%